Tent-Poles of the Bestseller: How Cross-media Storytelling can spin off a Mainstream Bestseller - Jensen, Thessa; Vistisen, Peter (Academic Quarter | Akademisk kvarter, 2013)
This article proposes a framework for understanding and analysing how the passive audience of a media event turns into active stakeholders. The starting point is the cross-media content quadrant (Jensen and Vistisen, 2012), which shows how the producer’s control is distributed on social media platforms, while storytelling evolves around a tent-pole, for example, a bestseller or blockbuster. To further explain how the audience engages, a three-step rhetoric model largely based on Bitzer (1998) and Tolkien (1971) is developed and explained.